The Anthropomorphized Emotional Profile of a (Un) Healthy Tooth - Maria do Rosario Dias; Samir Ahmad; Helcília Dias dos Santos; Maria Calejo Pires; Ana Ferreira; Valter Alves; Ana Delgado (European Scientific Journal, ESJ, 2020)
Drawing as a projective technique allows the access to the child's intrapsychic experiences. Notoriously, the use of drawings has been known as a referential research instrument in qualitative Health studies. Objectives: This exploratory study aims at understanding the mental representation of the concept of a healthy tooth and of an unhealthy tooth, through anthropomorphized drawings made by children, aged 6-12 years. Methods: The sample consisted of 150 children of both genders who attended at least one dental appointment at a University Dental Clinic of a metropolitan urban area. Drawings that showed anthropomorphized teeth (n = 300) were selected to perform the content analysis of the anthropomorphized features. Results: There is a clear variation in the level of anthropomorphizing of teeth according to age and gender. Conclusion: The results point to an increase in subject’s mental representation of reality in drawings in accordance to subject’s age, most significantly from 10 years onwards.